Improved and automated krypton assay for low-background xenon detectors with Auto-RGMS - Guida, Matteo; Lin, Ying-Ting; Simgen, Hardy (The European physical journal. C, Particles and fields, 2025)
Ultra-sensitive quantification of trace radioactive krypton-85 ( 85 Kr) is essential for low-background experiments, particularly for next-generation searches of galactic dark matter and neutrino physics using xenon-based time projection chambers (TPCs). While the rare gas mass spectrometer (RGMS) represents the current state-of-the-art for krypton detection in the field, we are developing a fully automated system (Auto-RGMS) to overcome the limitations of its manual operation. Auto-RGMS incorporates a robust control system for rapid measurements and minimized systematic uncertainties. A primary goal is to reach detection limits in the low parts-per-quadrillion (ppq) range for natural krypton by improving the chromatography stage to enhance the separation of krypton from xenon. Investigations into various adsorbent materials identified two candidates. HayeSep Q offers a 12-fold improvement in chromatographic resolution for xenon/krypton separation compared to the previously used adsorbent. Alternatively, HayeSep D provides a more limited improvement in resolution while allowing a higher measurement frequency because of its moderate retention-induced contamination after each measurement. By automating krypton assays and achieving ppq sensitivity, Auto-RGMS will be an indispensable tool for next-generation detectors, maximizing their scientific potential.